Staged treatment of abdominal sepsis in a puerpera with COVID-19 and pancreatonecrosis after cesarean section: case report - E. G. Grigoryev; L. V. Sereda; N. I. Ayushinova (Acta Biomedica Scientifica, 2022)
The aim of the study. Description of the medical history and discussion of treatment tactics in a puerperal woman after a caesarean section against the background of pancreatic necrosis, panmetritis, abdominal sepsis, COVID-19.Material and methods. A 30-year-old pregnant woman (30–31 weeks) was hospitalized in a perinatal center 5 days after the onset of girdle pain in the abdomen and uncontrollable vomiting, which did not bring relief. She had a history of caesarean sections 10 and 5 years ago. Sterile pancreatic necrosis was diagnosed. Successful caesarean section was performed. During the revision of the abdominal cavity, multiple plaques of fatty necrosis, omentobursitis were found in the upper abdomen. The treatment included pancreatic abdominization, cholecystostomy, abdominal drainage. Clinical roentgenologic examination and PCR-test verified COVID-19.Infected pancreatonecrosis developed, complicated with necrotic omentitis, abscess of the omental bursa (Enterococcus faccilis 107 CFU, Acinobacter baumani 106 CFU), abdominal sepsis, successfully treated. During vaginal examination, hemorrhagic discharge appeared (Klebsiella pneumoniae 105 CFU, Pseudomonas aeruginosa 105 CFU). Extirpation of the uterus revealed the defect of the anterior wall, thrombosis of the uterine arteries and veins, peripheral vessels. The patient recovered. The body build index was 26.03 kg/m2 at admission, 18.22 kg/m2 – at discharge, 23.61 kg/ m2 – 3 months later.Conclusion. 1. During the COVID-19 pandemic, pregnant women are often targeted by SARS-CoV-2. Prevention, diagnosis and treatment of coronavirus infection should be carried out according to the recommendations approved by the authorized health organ. 2. In the presented case report, the pathogenesis of complicated sterile pancreatonecrosis, cesarean section, abdominal sepsis were significantly influenced by changes due to organ ischemia in the result of peripheral vessels thrombosis. 3. The severity of the patient’s condition was certainly determined by the miscellaneous microbial profile – association of four agents of aggressive in-hospital infection in high concentration.